2011
DOI: 10.3109/10826084.2011.631962
|View full text |Cite
|
Sign up to set email alerts
|

How Does Youth Cigarette Use Respond to Weak Economic Periods? Implications for the Current Economic Crisis

Abstract: This paper examines whether youth cigarette use increases in weak economic periods (as do youth alcohol and drug use). The data come from the 1997 National Longitudinal Survey of Youth. With repeated measures over the 1997-2006 period, for almost 9000 individuals, the samples include: 30,000+ teenagers (15-19) and 30,000+ young adults (20-24). Logit models with state and year controls are estimated. The results indicate that teenagers and young adults increase cigarette use when the economy is weaker, implying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Our study should inform the policy debate about the broader welfare effects of minimum wage increases. 1997, 1998, 2002AL 1997, 1998, 2007AR 1996, 1997, 2007AZ 1997, 1998, 2007, 2011, 2012CA 1996, 1997, 1998, 2002, 2007CO 1996, 1997, 2007, 2011, 2012CT 1996, 1997, 1999, 2001, 2002, 2003, 2006, 2007DC 1994, 1997, 1998, 2005, 2012DE 1996, 1997, 1999, 2007FL 1996, 1997, 2006, 2007, 2012GA 2001HI 1992, 1993, 2002…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study should inform the policy debate about the broader welfare effects of minimum wage increases. 1997, 1998, 2002AL 1997, 1998, 2007AR 1996, 1997, 2007AZ 1997, 1998, 2007, 2011, 2012CA 1996, 1997, 1998, 2002, 2007CO 1996, 1997, 2007, 2011, 2012CT 1996, 1997, 1999, 2001, 2002, 2003, 2006, 2007DC 1994, 1997, 1998, 2005, 2012DE 1996, 1997, 1999, 2007FL 1996, 1997, 2006, 2007, 2012GA 2001HI 1992, 1993, 2002…”
Section: Discussionmentioning
confidence: 99%
“…In addition, job loss increases both sedentary activity (television watching), which may harm health, and rest, which may improve health. Additional research in this area provides similarly mixed findings (Ruhm 2005;Xu and Kaestner 2010;Charles and DeCicca 2008;Arkes 2012;Arkes 2007). Collectively, these studies suggest that, although reduced time costs offer individuals the opportunity to improve health through nonmarket, time-intensive good investments, the extent to which workers engage in such investments is not clear.…”
Section: Time Costsmentioning
confidence: 97%
“…[7][8][9][10][11][12] On the other hand, some of the most recent studies based on ex-post analysis of smoking behaviour after the 2008 financial crisis reported a null or even a counter-cyclical relationship (the crisis increased tobacco smoking), possibly explained by an increased psychological stress in selected vulnerable populations. [13][14][15][16][17][18][19][20] In the UK, for instance, the attempt rates for smoking cessation steadily declined after the onset of the economic crisis. 21 In Italy, the crisis had dramatic socio-economic consequences: unemployment rate has increased from 6.1% in 2007, to 10.7% in 2012 and up to 12.7% in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that during previous economic downturns, some teenagers engaged more than usual in risky health behaviors such as substance abuse and sexual activity (Arkes 2007(Arkes , 2012; Arkes and Klerman 2009;Levine 2001). Arkes (2009) also found changes in teenage weight over the business cycle, with male teenagers losing weight and female teenagers gaining weight in weaker economic periods.…”
mentioning
confidence: 99%
“…Arkes 2007Arkes , 2012; Arkes and Klerman 2009;Ruhm 2000) that examined how changes in the economy affect behavior, the econometric model in this paper includes both state and year fixed effects, thus exploiting the variation in unemployment rates among states over time in order to identify the relationship between state-level unemployment rates and teenagers' health behaviors and also between state-level unemployment rates and teenagers' time use, while controlling for national trends and time invariant differences across states. I use state-level unemployment rates to proxy for macroeconomic conditions in order to identify the total effects of the economy on teenagers' activities.…”
mentioning
confidence: 99%